2000
DOI: 10.1034/j.1600-051x.2000.027010753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormonal contraceptives on the periodontium, in a population of rural Sri‐Lankan women

Abstract: Usage of contraceptive preparations containing oestrogen and progesterone resulted in hormonal changes similar to those seen in pregnancy, associated with increased prevalence of gingivitis. There was significantly higher LA with prolonged usage of hormonal contraceptives, compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 23 publications
7
48
0
2
Order By: Relevance
“…The most pronounced periodontal changes occur during pregnancy, as a significant proportion of pregnant women suffer from pregnancy gingivitis. Women on hormonal replacement therapy (HRT) and oral contraceptives experience increased gingival inflammation [81, 99]. With oral contraceptives, this increase in gingival inflammation is mainly related to the duration of use as it has been suggested that prolonged use of oral contraceptives may detrimentally affect the periodontium.…”
Section: Risk Factors Of Periodontal Diseasementioning
confidence: 99%
“…The most pronounced periodontal changes occur during pregnancy, as a significant proportion of pregnant women suffer from pregnancy gingivitis. Women on hormonal replacement therapy (HRT) and oral contraceptives experience increased gingival inflammation [81, 99]. With oral contraceptives, this increase in gingival inflammation is mainly related to the duration of use as it has been suggested that prolonged use of oral contraceptives may detrimentally affect the periodontium.…”
Section: Risk Factors Of Periodontal Diseasementioning
confidence: 99%
“…However, it should be emphasized that there are reports of the presence of estrogen and progesterone receptors in the periodontal tissues 25,26 making alterations on cytokine and prostaglandin production in association with disturbances in the microvascular system and higher levels of certain bacterial species, as a result of the effects of higher serum levels of sex hormones during the use of oral contraceptives. These arguments are supportive to the belief that women taking this medicine are more susceptible to the development and progression of periodontal diseases 2,10,11,14,16,24 .…”
Section: Discussionmentioning
confidence: 69%
“…Tilakaratne, et al. 24 (2000) investigated 32 women taking hormonal contraceptives for less than 2 years, 17 of them for 2-4 years and a matched control group of 39 women not taking the medication. The results obtained suggested that women taking pills had similar oral hygiene levels than women who did not take.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease prevalence among women of reproductive age is estimated to be 37% to 46% and can be up to 30% among pregnant women (New York State Department of Health, 2006). Although pocket depth (an increase in pocket depth is a marker for clinical periodontal disease) around teeth has been shown to increase as pregnancy progresses, this increase resolves after birth if it is caused by hormonal changes during pregnancy (Tilakaratne et al, 2000) rather than periodontal destruction (Miyazaki et al, 1991).…”
Section: Periodontal Disease During Pregnancymentioning
confidence: 99%